2017
DOI: 10.1186/s12870-017-1038-y
|View full text |Cite
|
Sign up to set email alerts
|

Global identification, structural analysis and expression characterization of bHLH transcription factors in wheat

Abstract: BackgroundBasic helix-loop-helix (bHLH) transcription factors (TFs), which are widely distributed in eukaryotic organisms, play crucial roles in plant development. However, no comprehensive analysis of the bHLH family in wheat (Triticum aestivum L.) has been undertaken previously.ResultsIn this study, 225 bHLH TFs predicted from wheat using genomic and RNA sequencing data were subjected to identification, classification, phylogenetic reconstruction, conserved motif characterization, chromosomal distribution de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 50 publications
5
40
0
Order By: Relevance
“…The 19 subfamilies were designated I a, I b, II, III a, III b, III c, III d+e, III f, IV a, IV d, V a, V b, VII a+b, VIII a, VIII b+c, IX, X, XI, and XII ( Fig 1 ). Most of these subfamilies are common and are consistent with the subfamily classification reported in previous phylogenetic analyses in other plant species, such as tomato [ 9 ], peanut [ 8 ], Chinese cabbage [ 13 ], and wheat [ 27 ]. This finding indicated that the bHLH proteins in the conserved subfamilies among plant species may play a fundamental role during plant development and evolution.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The 19 subfamilies were designated I a, I b, II, III a, III b, III c, III d+e, III f, IV a, IV d, V a, V b, VII a+b, VIII a, VIII b+c, IX, X, XI, and XII ( Fig 1 ). Most of these subfamilies are common and are consistent with the subfamily classification reported in previous phylogenetic analyses in other plant species, such as tomato [ 9 ], peanut [ 8 ], Chinese cabbage [ 13 ], and wheat [ 27 ]. This finding indicated that the bHLH proteins in the conserved subfamilies among plant species may play a fundamental role during plant development and evolution.…”
Section: Resultssupporting
confidence: 86%
“…Compared with the number of bHLH genes identified in other plant species in previous studies, fewer bHLH superfamily genes were identified in peach in this study. In previous studies, 132, 124, 188, 225, 155, 167, 146 and 159 bHLH genes were identified in peanut [ 8 ], potato [ 26 ], apple [ 10 ], wheat [ 27 ], bean [ 17 ], rice [ 4 ], carrot [ 28 ], and tomato [ 9 ], respectively. These values are probably associated with differences in evolution and genome duplication or genome sizes in these plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A. The backbones of motif 1 and 2 are also conserved among plant species [10,20,47], which is believed to indicate that these highly conserved residues in bHLH domains are responsible for dimerization [10].…”
Section: Phylogenetic Analysis Gene Structure Conserved Motifs Analmentioning
confidence: 98%
“…The earliest reported bHLH protein in animals is the mouse transcription factors E12 and E47 (Murre et al, 1989;Massari and Murre, 2000;Stevens et al, 2008;Murre, 2019). Later studies suggested the animal bHLH proteins to be divided into six large categories of protein subclasses that were subdivided as 45 sub-families (Ledent and Vervoort, 2001;Ledent et al, 2002;Simionato et al, 2007;Stevens et al, 2008;Wang et al, 2010), whereas the plant bHLH proteins were divided into more than 20 subclasses with conserved motifs or domains identified (Carretero-Paulet et al, 2010;Yan et al, 2015;Liu et al, 2018;Wei and Chen, 2018;Gao et al, 2019), varying from 21 to 32 subfamilies (Carretero-Paulet et al, 2010;Song et al, 2014;Hudson and Hudson, 2014;Sun et al, 2015;Yan et al, 2015;Zhang et al, 2015;Kavas et al, 2016;Gao et al, 2017;Guo and Wang, 2017;Niu et al, 2017;Liu et al, 2018;Lu et al, 2018;Wei and Chen, 2018;Gao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%